Correlation between variables of therapeutic interaction with clients in SAD - Garcia, Vagner Angelo; Bolsoni-Silva, Alessandra Turini; Nobile, Glaucia Fernanda Galeazzi (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
Several studies have been developed for therapeutic interaction, however the population with Social Anxiety Disorder (SAD) is still little studied in this research field. This study aimed to analyze the correlations between variables of the therapeutic process: therapist and client behaviors and the themes discussed in the sessions. Participated in the research two clients diagnosed with SAD and a therapist. The sessions were analyzed using a categorization system behavior, and the correlation analysis by means of Spearman's rho test were performed. The results indicate that the therapist presented a therapy in active listening, being empathetic to provide information and recommendations. Sought information on certain topics with empathy, collecting data and asking for consideration. Another highlight is the correlation between Relations and Goals/Concordance, which configure as key processes to achieve the therapeutic goal.